Religion and the Metaphysical Search of Modern Man - SZULAKIEWICZ, MAREK (Filozofia Chrześcijańska, 2018)
Contemporary post-metaphysical culture undertook the express fi ght against absoluteness and universality by propagating and defending pluralism. It seemed that if instead of the quest for what is universal and absolute there will be almost infi nite magnitude of views, opinions, meanings etc., everybody will fi nd something for himself what will be his own meaning. The loss of the reference to what is absolute and universal led though to the loss of concrete goals, values and meanings. But we cannot “manage diversity” if we lack this reference. What is more, the world becomes closed and limited and it recedes to the static and locked-in state in which admittedly everything is in fl ux, views are being liberally changed, meanings accepted and rejected depending on the moment, but actually everything is motionless in the closed world. If we know all of this and deeply experience the crisis of the meaning of existence that stems from the rejection of metaphysics and from the surrender of culture to the most important questions and to boot fragmentation of reality becomes dangerous and destructive, then the revival of metaphysical thinking becomes the need of our world. The man itself is not enough; neither the culture that tantalises itself with selfsuffi ciency; both of them lose the meaning of their existence. Man cannot indefi nitely recede from the world. On the contrary, he has to place this world within some meaningful order. All these needs are metaphysical. The quest for the foundation of all meaning has been the essence of metaphysics for ages. That is why we experience not only longing for metaphysics but we also enter the way of the search for it. However, before the quest for metaphysics there are metaphysical quests which purpose is to recall questions and to slowly teach the man these questions anew. For we are bonded with the absolute – not necessarily with the “existence of the absolute” but inescapably with “questions about it”.